2003
DOI: 10.1007/s00464-002-9184-0
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous fetoscopic patch coverage of experimental lumbosacral full-thickness skin lesions in sheep

Abstract: Percutaneous fetoscopic posturing and patch coverage of lumbosacral full-thickness skin lesions can effectively and safely be achieved in sheep. This approach promises to provide a substantial reduction of maternal trauma from fetal surgery for myelomeningoceles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 18 publications
0
36
0
3
Order By: Relevance
“…This subdermal placement of the interface material enables the lesion to be covered with skin, eliminating the need to affix a patch to an adjacent structure, as done by Eggink et al 6 , Paek et al 17 , Bouchard et al 18 and Kohl et al 25 . In initial studies by Copeland et al 24 only a skin defect were created to study different materials and techniques for correction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This subdermal placement of the interface material enables the lesion to be covered with skin, eliminating the need to affix a patch to an adjacent structure, as done by Eggink et al 6 , Paek et al 17 , Bouchard et al 18 and Kohl et al 25 . In initial studies by Copeland et al 24 only a skin defect were created to study different materials and techniques for correction.…”
Section: Discussionmentioning
confidence: 94%
“…In others, only the skin was removed, without involving muscle or any other planes below this level 6,24,25 . Observe that correction was sometimes performed a few weeks after the defect's creation and sometimes the defect was created and corrected at the same time 6,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…In all these studies, the authors based their observations on analyses of the anatomical specimen, which is a lot more troublesome to prepare than what is needed to submit the samples to resonance, in our study. After the beginning of our study, four more studies were published in which myelomeningocele was surgically created in a sheep fetus, three of them from the same group of authors in San Francisco, United States [14][15][16]18 . All of them demonstrated that the defect created by this technique is histologically similar to myelomeningocele in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In the second study 10 , we successfully developed a new corrective technique, using cellulose film to cover the deformity. Because of its similarity with the human fetus in size and anatomy, the ovine fetus has been the animal model of choice for developing new techniques in fetal surgery 7,[11][12][13][14][15][16][17][18] . Therefore, this corrective technique should be subsequently applied in ovine fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal morbidity associated with open correction suggests that minimally invasive methods are the future of antenatal correction of myelomeningocele. Some authors have studied the endoscopic correction of this defect both in animal models (14)(15)(16) and in humans (17) -in…”
Section: Discussionmentioning
confidence: 99%